The role of seasonality and non‐lethal carry‐over effects on density‐dependent dispersal. Issue 12 (15th December 2015) - Betini, Gustavo S.; Pardy, Aaron; Griswold, Cortland K.; Norris, D. Ryan
Abstract : Understanding dispersal is critical for predicting a wide range of ecological dynamics. Variation in intraspecific density is widely regarded as a major factor influencing dispersal rates but it is not clear why dispersal is positively related to density in some systems and negatively related to density in other systems. Using seasonal populations of Drosophila melanogaster, we experimentally show that dispersal rates are both positively related to breeding density at the time of dispersal and negatively related to density at the beginning of the previous non‐breeding season. This suggests that flies use density at the time of dispersal as a cue for habitat quality but are also negatively influenced by the delayed, non‐lethal effects of density in the previous season. A parameterized model indicates that a carry‐over effect not only causes a decrease in the proportion of individuals that disperse, but also a decrease in population size caused by lower per capita breeding output. Our results demonstrate how density can have contrasting effects on dispersal and population size depending on when density is measured in the annual cycle and that non‐lethal effects on individuals can have important, but previously unrecognized, consequences for both the movement rates and long‐term dynamics of seasonal populations.